GODS AND TEMPLES: SEARCHING OF HUMAN VALUES WITH SPECIAL REFERENCE TO RASHTRASANT TUKADOJI MAHARAJ’S GRAMGEETA - Sarode, Yogesh M (International Journal of Psychosocial Rehabilitation, 2020)
Abstract India is a country of many countries in which people of different religions, castes and creeds live together. They have different languages, apparels, food, taste and preferences. In spite of these every Indian consider our country as motherland. ‘Unity in diversity’ is discerned through each and every activity of Indians. The human values are nurtured in Indian people with the spirit of brotherhood and message of universal peace by the great saints and sagesnow and then.Rashtrasant Tukadoji Maharaj prophesies the appliedmethod of rebuilding of villages. The worship systems of different sects, their oppositions,quarrels and reactions hamper the progress of village. The Indian have strong sentiments about God and easily put blind faith on religious institutions. The priests in the religious institutions have major role to perform in moral stability of any society. But it seems that these priests have different concepts according to their sects and thereforeplay different roles in the name of unification of Gods; hence their nature and actionsvary. Temples are centers of imbibing moral values. If these religious institutions are mended properly, human society would definitely prosper. Hence an honest effort has been made through this paper to focus on human values through the spectacle of Gramgeeta as to how humans can correct and enhance the living by mending principles of life to make this planet a better place.